Effects of Different Anti-Epileptic Drug Groups and Brushing on the Color Stability of Restorative Materials Used in Pedodontics: An In Vitro Evaluation - Mehmet Sinan Dogan; Şemsettin Yıldız (MDPI AG, 2024)
Objectives: This study will evaluate the effects of anti-epileptic drugs and brushing used in children on the color change of three restorative materials by creating an in vitro study model. Methods: Forty samples of polyacid-modified composite resin (compomer), glass ionomer cement (GIC), and composite resin (CR) were prepared. Samples were split into four groups (n = 10) and soaked in three anti-epileptic drugs (Tegretol, Depakine, Keppra) and distilled water. For each group (n = 5), two subgroups (brushing and non-brushing) were created. Discolorations [CIEDE2000 (ΔE00)] were determined initially and on days 7 and 14. The data were analyzed with a four-factor repeated measures ANOVA analysis, and a post hoc analysis Bonferroni test was used. Results: After the second week, the highest ΔE00 value was seen in the non-brushed compomer material in the Tegretol drug group (8.59 ± 0.43). In contrast, the lowest value was seen in GIC filling material-brushing-Depakine drug (3.45 ± 2.14). ΔE00 values in the brushing groups were statistically significantly lower than those in the no brushing groups (p < 0.05). Conclusions: It has been determined that the color stability of aesthetic restorative dental materials used in pediatric dentistry is affected by antiepileptic drugs. In addition, it has been determined that tooth brushing positively affects the color stability of restorative materials. Therefore, pediatric dentists should advise their patients and their relatives about this issue and take precautions.